Grieving to Heal: Analyzing Grief in Zauner’s Memoir Crying in H Mart (2021) - Meutia Nur Izzani Aziz; Isti Gandana (Humanitatis : Journal of Language and Literature, 2024)
Grief is a universal human experience that has become a recurring theme in various literature genres, especially in memoirs. This study aims to discover how grief is portrayed in a contemporary memoir. Using Kübler-Ross and Kessler (2014)’s five stages of grief, this qualitative study examines the embodiment of grief as expressed by the main character, Michelle, in the memoir Crying in H Mart (2021). The method of this study is qualitative approach. This research results reveals Michelle to have undergone the five stages of grief: denial, anger, bargaining, depression, and acceptance. Certain stages, however, were found to be more prominently expressed by the main character. This study is expected to provide contribution on better awareness and understanding of grief and its impacts on individuals and our modern societies.